Catheter-associated urinary tract infection: signs, diagnosis, prevention. (24th January 2019) - Davis, Cathy
Abstract : Catheter-associated urinary tract infection (CAUTI) is one of the most prevalent healthcare-associated infections (HAIs) in the UK and can have implications for both the patient and the health service. This article highlights those at risk, the signs and symptoms of CAUTI, diagnosis, methods of prevention and treatment. It highlights current guidance available to nurses to help ensure they are following the most recent recommendations for best practice.